Infection indices of Camallanus cotti Fujita, 1927 in Tor putitora in Mahakali River, Nepal - Joshi, Yagya Raj; Joshi, Promod (Nepalese Journal of Zoology, 2023)
Red worm (Camallanus cotti Fujita, 1927) is an intestinal parasite both in wild and cultured fish all over the world. This study aimed to investigate the prevalence and mean intensity of red worms in Mahseer (Tor putitora) in Mahakali River, Nepal. The study was conducted from October 2021 to February 2023. Mahseer fish (n=211) were collected from two sites of the river using gill nets and also purchased from the local markets of respective sites assuring the fish were from the Mahakali River. Parasites were recovered and processed using standard helminthological methods. Overall, the prevalence and mean intensity of the red worms in Mahseer were 3.79% and 1.37, respectively. The highest prevalence was found in more than 0.2 m long (4.38%), 0.051–0.1 kg weighted (6.42%) female host fish (4.32%) in March (22.22%) and spring seasons (5.26%). Similarly, the highest intensity was found in 0.1–0.2 m long (2), 0.051–0.1 kg weighted (1.42) female host fish (1.37) in January (4) and winter season (2). Statistically, the variation in prevalence and intensity of the parasite were insignificant (p˃ 0.05). This study reveals low infection of the red worm in Mahseer but increases the risk of dissemination of parasites from the Mahakali River to nearby fish farms.